2018
DOI: 10.3390/nu10111580
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Preventive Role of Isolated Phytoconstituents: Findings from a Decade of Research

Abstract: Cataract is an eye disease with clouding of the eye lens leading to disrupted vision, which often develops slowly and causes blurriness of the eyesight. Although the restoration of the vision in people with cataract is conducted through surgery, the costs and risks remain an issue. Botanical drugs have been evaluated for their potential efficacies in reducing cataract formation decades ago and major active phytoconstituents were isolated from the plant extracts. The aim of this review is to find effective phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 136 publications
(196 reference statements)
0
11
0
1
Order By: Relevance
“…Scientific reports based on observational studies indicate that a well-balanced diet rich in vegetables and fruits, containing about 150 g of protein, high intake of vitamin C, vitamin E, and a reduced amount of simple sugars, as well as supplementation with other vitamins or carotenoids, may contribute to delaying the cataract progression [31]. According to the in vitro and in vivo experiments, dietary components derived from medicinal plants, such as flavonoids, phenolic acids, terpenes, carotenoids or phytosterols, seem to be effective in preventing opacity of the lenses [22,23,31]. They can act through various mechanisms, of which the most important is anti-oxidative and anti-glycating activities [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific reports based on observational studies indicate that a well-balanced diet rich in vegetables and fruits, containing about 150 g of protein, high intake of vitamin C, vitamin E, and a reduced amount of simple sugars, as well as supplementation with other vitamins or carotenoids, may contribute to delaying the cataract progression [31]. According to the in vitro and in vivo experiments, dietary components derived from medicinal plants, such as flavonoids, phenolic acids, terpenes, carotenoids or phytosterols, seem to be effective in preventing opacity of the lenses [22,23,31]. They can act through various mechanisms, of which the most important is anti-oxidative and anti-glycating activities [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that both rosmarinic acid and sinapic acid had a positive effect on parameters related to glucose and lipid metabolism, as well as on some parameters of oxidative stress in the serum of ovariectomized rats in the early phase of estrogen deficiency [20,21]. Based on various experimental in vitro and in vivo animal studies, there are also suggestions on the possibility of using phenolic acids, including rosmarinic acid, to reduce cataract development [22,23,24,25]. However, there is still no data on the effects of plant-derived antioxidants, including rosmarinic and sinapic acid on oxidative stress parameters in the lenses exposed to estrogen deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Statistics from the World Health Organization (WHO) indicate that cataract is the primary cause of about 90% of blindness in people living in the developing world [2]. Cataract surgery involving the removal of lens and correction of eyesight with eye glasses or an intraocular corrective lens remains the most successfully developed treatment option for cataract [1,3,4]. However, the cost of surgery and aftermath complications of the surgical procedure remain a burden to both patients and surgeons [5].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms which could be comprised in diabetic cataract include polyol pathway flux, osmotic stress, elevated oxidative stress, and increased formation of AGEs [11]. Potential therapeutics to reduce dicarbonyls and AGE formation have to be improved at scavenging dicarbonyls, alternative pathways for the diminution of AGE formation, for example, transition metal chelation to decrease the autoxidative fragmentation of glucose may be pursued [12].…”
Section: Introductionmentioning
confidence: 99%